2009
DOI: 10.3233/jad-2009-1062
|View full text |Cite
|
Sign up to set email alerts
|

Altered Subcellular Distribution of c-Abl in Alzheimer's Disease

Abstract: Abstractc-Abl is a non-receptor tyrosine kinase that participates in multiple signaling pathways linking the cell surface, cytoskeleton, and the nucleus. Recent in vitro studies have also linked c-Abl to amyloid-β-induced toxicity and tau phosphorylation. To further characterize a potential role of c-Abl in Alzheimer's disease (AD), we examined the expression and distribution of total and phosphorylated forms of c-Abl in the hippocampus of AD and control subjects. Laser scanning confocal microscopy was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…A growing body of evidence indicates that c-Abl inhibitor could suppress neurotoxicity and neuroinflammation in experimental models of PD and AD (Jing et al, 2009; Estrada et al, 2011; Karuppagounder et al, 2014; Brahmachari et al, 2016). In an effort to assess the anti-inflammatory effects of DAS, a dual c-Abl/c-Src kinase inhibitor (Lombardo et al, 2004), we used the LPS-stimulated BV2 microglial cells as a model of neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence indicates that c-Abl inhibitor could suppress neurotoxicity and neuroinflammation in experimental models of PD and AD (Jing et al, 2009; Estrada et al, 2011; Karuppagounder et al, 2014; Brahmachari et al, 2016). In an effort to assess the anti-inflammatory effects of DAS, a dual c-Abl/c-Src kinase inhibitor (Lombardo et al, 2004), we used the LPS-stimulated BV2 microglial cells as a model of neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, c-Abl has also been implicated in the CNS development, including neurogenesis, neurite outgrowth, and neuronal plasticity (Moresco and Koleske, 2003; Moresco et al, 2003). A growing body of evidence from several experimental model systems has also demonstrated that c-Abl is activated in neurodegenerative diseases including Alzheimer's disease (Cancino et al, 2008; Jing et al, 2009; Tremblay et al, 2010), Parkinson's disease (Ko et al, 2010; Imam et al, 2011; Mahul-Mellier et al, 2014) and synucleinopathies (Estrada et al, 2011). In this context, c-Abl has been shown to promote tyrosine phosphorylation of parkin in the N-terminal domain, and STI-571, a c-Abl kinase inhibitor has been shown to inhibit tyrosine phosphorylation thereby maintaining in a catalytically active and protective state (Ko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…modulation of actin cytoskeleton and c-Abl activation. A growing body of evidence indicates that diverse neurological disorders, including Alzheimer disease and brain ischemia, are accompanied by altered levels of c-Abl and actin (51)(52)(53)(54)(55)(56)(57). Hence, the insight that Mt3 plays a role in c-Abl activation and actin dynamics may suggest new therapeutic strategies for such neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have implicated abnormally activated Abl kinases in multiple neurodegenerative diseases (reviewed in Schlatterer et al, 2011) (Jing et al, 2009;Ko et al, 2010). Pharmacological inhibition of Abl kinases in both Alzheimer's disease (AD) and Parkinson's (PD) disease models facilitates amyloid clearance and reduces neuro-inflammation, two key drivers of neuronal cell death.…”
Section: Role For Abl Kinases In Neurodegenerative and Inflammatory Dmentioning
confidence: 99%